Trauma-informed care in emergency medicine: The role of nurses, pharmacy, telehealth in providing care to patients who have experienced trauma - Alanazi, Seham Ahmed; Almanna, Mohammad Abdullah; Alanazi, Dhiyaa Manawer; Enazi, Sami Mohammed Al; Alaboush, Khalid Salem; Alaujan, Badour Subhi; Zamzami, Bander Ahmad; Alsaleh, Wadha Abdulkarim (International journal of health sciences, 2023)
Background: The COVID-19 pandemic has accelerated the adoption of telehealth in healthcare, particularly in emergency medicine. The need to minimize physical contact and optimize resource allocation has led to the exploration of telehealth's potential in pre-hospital, inpatient, and post-discharge settings. Aim of Work – This review examines the utilization of telehealth and the role of physicians, nurses, and pharmacists in emergency medicine during the COVID-19 pandemic, highlighting its applications, benefits, and limitations. Methods – A comprehensive electronic search was conducted across six databases (PubMed, Web of Science, Scopus, MEDLINE, Cochrane Library, and Embase) up to 2018. The review focused on English-written, full-text articles that explored telehealth in emergency medicine. A total of 36 articles were selected for analysis. Results – Telehealth has demonstrated its value in pre-hospital care, emergency department (ED) management, and post-discharge follow-up. Key applications include remote patient monitoring, virtual consultations, and tele-triage. Benefits include reduced PPE usage, improved patient communication, and enhanced resource utilization. However, challenges include infrastructure limitations, technical issues, and ethical considerations. Conclusion – Telehealth holds significant potential to enhance emergency medical care, particularly in the context of infectious disease outbreaks. However, further research is needed to address existing limitations and optimize its implementation.